2007
DOI: 10.1371/journal.pone.0000987
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Inhalation Induces Dose-Dependent and Age-Related Negative Affectivity

Abstract: BackgroundCarbon dioxide inhalation is known to induce an emotion similar to spontaneous panic in Panic Disorder patients. The affective response to carbon dioxide in healthy subjects was not clearly characterized yet.Methodology/Principal FindingsSixty-four healthy subjects underwent a double inhalation of four mixtures containing respectively 0, 9, 17.5 and 35% CO2 in compressed air, following a double blind, cross-over, randomized design. Affective responses were assessed according to DSM IV criteria for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 38 publications
5
59
1
1
Order By: Relevance
“…Differently from Griez et al [41], who found older age associated with a decreased sensitivity to CO 2 in healthy volunteers, we were able to find only a mild, similar trend, possibly due to the narrower age range of our subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Differently from Griez et al [41], who found older age associated with a decreased sensitivity to CO 2 in healthy volunteers, we were able to find only a mild, similar trend, possibly due to the narrower age range of our subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Dizziness, sensation of shortness of breath, feeling of choking, and palpitations had the highest mean scores in all three CO 2 conditions (high, medium, and low). For both the eVAAS score and the PSL-IV total score, a statistically significant dose-response relationship was observed (these results are extensively presented elsewhere) (Griez et al, 2007). Each PSL symptom score was significantly dosedependent (po0.05).…”
Section: Resultsmentioning
confidence: 63%
“…We recently showed that increasing concentrations of CO 2 dose dependently induce a negative affect, which eventually culminates in genuine panic, also in healthy individuals (Griez et al, 2007). Accordingly, high doses of CO 2 may be considered as a model of panic in healthy subjects, just as moderate doses are in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A likely reason for the wide application of inhalation of CO 2 -enriched air is that it induces an increase in ventilation, escalating symptoms of arousal (Millhorn and Eldridge, 1986), and concomitant negative affect (Griez et al, 2007) in a dose-dependent way. In healthy volunteers, concentrations of 5 up to 7.5% CO 2 -enriched air for 2 min have been used to elicit mild transient physical symptoms such as increased ventilation, shortness of breath, feelings of warmth, sweating, and dizziness (Devriese et al, 2006;Stegen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%